2020
DOI: 10.3389/fimmu.2020.00793
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegaloviruses and Macrophages—Friends and Foes From Early on?

Abstract: Starting at birth, newborn infants are exposed to numerous microorganisms. Adaptation of the innate immune system to them is a delicate process, with potentially advantageous and harmful implications for health development. Cytomegaloviruses (CMVs) are highly adapted to their specific mammalian hosts, with which they share millions of years of co-evolution. Throughout the history of mankind, human CMV has infected most infants in the first months of life without overt implications for health. Thus, CMV infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 238 publications
(245 reference statements)
0
17
0
Order By: Relevance
“…18,19 Lytic gene expression and infectious virus production in alveolar macrophages of CMV seropositive patients who had neither CMV DNAemia nor an inflammatory state have been observed 20 suggesting the alveolar macrophage may be an additional site of latent or persistent CMV infection in the lung. We hypothesize that in addition to latent load, organ-specific differences in donor tissue macrophage survival related to their ontogeny [21][22][23][24] and the dynamics of developing recipient chimerism in the donor organ 22,25 as macrophages are replenished by recipient monocytes when organs are injured at transplantation may contribute to differences in organspecific CMV transmission rates. 26 Recipient microchimerism may evolve slowly.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Lytic gene expression and infectious virus production in alveolar macrophages of CMV seropositive patients who had neither CMV DNAemia nor an inflammatory state have been observed 20 suggesting the alveolar macrophage may be an additional site of latent or persistent CMV infection in the lung. We hypothesize that in addition to latent load, organ-specific differences in donor tissue macrophage survival related to their ontogeny [21][22][23][24] and the dynamics of developing recipient chimerism in the donor organ 22,25 as macrophages are replenished by recipient monocytes when organs are injured at transplantation may contribute to differences in organspecific CMV transmission rates. 26 Recipient microchimerism may evolve slowly.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, tissue-resident macrophages are immediate targets of HCMV infection in various tissues. 70 Though these cells have been terminally differentiated, they are capable of altering their function in accordance to environmental stimuli, like those induced in infections. 71 Polarization of macrophages towards either pro-or antiinflammatory state prior to viral exposure, changes their vulnerability to infection.…”
Section: Regulatory Macrophage (Mregs)mentioning
confidence: 99%
“…These sites are occupied by tissue‐resident macrophages. Therefore, tissue‐resident macrophages are immediate targets of HCMV infection in various tissues 70 . Though these cells have been terminally differentiated, they are capable of altering their function in accordance to environmental stimuli, like those induced in infections 71 .…”
Section: Types Of Regulatory Immune Cellsmentioning
confidence: 99%
“…Importantly, MCMV entry into macrophages and viral dissemination from the lungs is dependent on MCMV-encoded chemokine 2 (MCK2) (Ma et al, 2021; Stahl et al, 2015), a CC-chemokine-like product of spliced ORF m131/129 (MacDonald et al, 1999). It has been reported that MCK2 attracts monocytes to the site of infection through CX3CR1 signaling (Daley-Bauer et al, 2014) and enables the virus to disseminate by abortively infected myeloid cells, including monocytes, macrophages, and/or dendritic cells (Baasch et al, 2020; Farrell et al, 2017; Zhang et al, 2021). Upon intranasal infection, MCMV disseminates primarily to salivary glands (Oduro et al, 2016; Stahl et al, 2015), an organ that allows viral persistence and shedding for transmission to new hosts.…”
Section: Introductionmentioning
confidence: 99%